(untitled) - Tạ, Thành Nam (Cần Thơ, 2011)
The study reported in this thesis aims at testing to what extent PPT enhances vocabulary performance of high school students and investigating learners’ attitudes toward the use of PPT in teaching and learning vocabulary
Keywords: Vocabulary,Ngôn ngữ tiếng Anh,Từ vựng,English language; Study and teaching,Dạy và học